2003
DOI: 10.1021/ma034042u
|View full text |Cite
|
Sign up to set email alerts
|

Shear Alignment at Two Length Scales:  Comb-Shaped Supramolecules Self-Organized as Cylinders-within-Lamellar Hierarchy

Abstract: Large-amplitude oscillatory shear alignment of a hierarchically ordered system of combshaped supramolecules and the preparation of core-corona nanorods thereof are reported. The supramolecules consist of nearly symmetric polystyrene-b-poly(4-vinylpyridine) diblock copolymers with pentadecylphenol side chains hydrogen bonded to the poly(4-vinylpyridine) blocks. The polystyrene blocks, accounting for approximately 20% (w/w) of the supramolecules, are segregated in hexagonally ordered cylinders inside a matrix fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…[12][13][14]18 In particular, corecorona nanorods can be easily prepared in this way with the core being formed by the majority (longest) rather than the minority block of the diblock copolymer used. 18,19 Recently, it was demonstrated that nanorods with a PS core and a P4VP corona, obtained via the comb-shaped supramolecules route, exhibit very poor mechanical properties. 20 The rods consisted of nearly symmetric PS-b-P4VP diblock copolymers with a molar mass of ca.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14]18 In particular, corecorona nanorods can be easily prepared in this way with the core being formed by the majority (longest) rather than the minority block of the diblock copolymer used. 18,19 Recently, it was demonstrated that nanorods with a PS core and a P4VP corona, obtained via the comb-shaped supramolecules route, exhibit very poor mechanical properties. 20 The rods consisted of nearly symmetric PS-b-P4VP diblock copolymers with a molar mass of ca.…”
Section: Introductionmentioning
confidence: 99%
“…weight fraction 23% vs PS) one obtains cylindrical self-assemblies. 17,18,52 In order to have overall alignment, shear flow processing by either large amplitude dynamic rheometry or, more practically, by an extruder allows high overall alignment. 17,19 Finally, the nanofibers forming the self-assembled cylindrical cores can be cleaved by selective polar solvent treatment using ethanol, thus releasing long individualized nanofibers with a PS core and a P4VP corona, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 However, towards the rational use of self-assemblies to construct nanofibers, conceptually perhaps the simplest model material is provided by diblock copolymers 15,16 with hexagonally self-assembled cylindrical cores which can be cleaved by selective solvent processes after shear alignment. [17][18][19] Such fibers can be postmodified by various ways 20 and we will describe inorganic modification using atomic layer deposition 21 which is a self-limiting sequential chemical vapour deposition concept. [22][23][24] This allows high precision both in the organic and inorganic parts of the hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the electrically conducting channels can be discontinuous at the domain boundaries. More generally, aligned and monodomain structures in block copolymers have been pursued using several concepts, for example using thin films where the surface energies play a major role, electric fields, magnetic fields, flow alignment and graphoepitaxy [86,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Therefore, in many of the applications requiring enhanced electrical transport, a generic goal in relation to self-assembly is to prepare monodomain structures having e.g.…”
Section: General Remarks On Polymeric Self-assembly In Relation To Elmentioning
confidence: 99%
“…nonpolar carbosilane block and rigid helical polyisocyanide blocks form complexes with silver ions and lead to nanowires [365]. Distinct nanowires can be achieved by using polystyrene-b-poly(4-vinylpyridine) where pentadecylphenol is hydrogen bonded to the pyridines, which leads to hierarchical self-assembly [366]: Polystyrene cylinders within poly(4-vinylpyridine)-pentadecylphenol can be obtained and, after aligning and removing the pentadecylphenol, distinct polystyrene wires with a poly(4-vinylpyridine) corona are obtained [86,109,367], which can be metallized with CdSe, Pd, Ag and Au [368,369]. The self-assembled domains of symmetrical polystyrene-b-poly(4-vinylpyridine) diblock copolymers have been used as templates to prepare Ag layers by electroless deposition and anisotropic conductivity was achieved along the lamellae [370].…”
Section: Self-assembly Of Conjugated Polymersmentioning
confidence: 99%